Policy and Practice of Village Fund Allocation and Agro-Downstreaming: Evidence from Wotay Village, Central Maluku - Sakir, Ahmad Rosandi; Ponto, Iriane Sosiawaty; Patty, Julia Theresia; Silawane, Naifa Nabila (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2026)
This study aims to analyze the Policy and Practice of Village Fund Allocation and Agro-Downstreaming: Evidence from Wotay Village, Central Maluku. Wotay Village is one of the second-largest coconut-producing areas in Maluku Province, with 221 farmers and coconut-processing business actors. A total of 70 respondents were selected from this population using purposive and simple random sampling. Data were collected through a five-point Likert-scale questionnaire and analyzed using multiple linear regression. The results show that Village Fund Allocation has no significant effect on community welfare, despite the village receiving IDR 757,282,000 in 2024, due to limited community participation, low transparency, and a predominantly top-down budgeting process. In contrast, Coconut Product Downstreaming has a positive and significant effect on welfare, as higher levels of processing and value addition contribute to increased income and improved living standards. Overall, both variables explain 47.2% of the variation in community welfare, emphasizing the need for effective downstreaming strategies and participatory, transparent Village Fund management to enhance sustainable welfare and support the development of village policies and local agro-industrial economic empowerment.